Directions of the foreign policy of the French Republic (2007-2017) - Oten, Г.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
This article offers an analysis of the main vectors and trends in the foreign policy of the Republic of France during the presidency of Nicolas Sarkozy and François Hollande. Along with this, it is proposed to analyze the priorities of France’s foreign policy and the activities of the two Presidents in the period 2007-2017. The diplomacy of France in the system of international relations and the peculiarities of its foreign policy course is one of the most difficult problems to study over the centuries. The French political course of the first half of the 21st century is a very urgent and complex issue on the agenda in the framework of regional and world politics.At the present time, in the period of intensive parallel development of integration and disintegration world processes, the study of the diplomatic course of influential superpowers is an important theoretical and practical task.